Effect of NaCl on the properties of Eu-doped Ca-α-SiAlON phosphors prepared by combustion synthesis. Issue 3 (15th February 2016) - Ge, Yiyao; Chen, Ying; Wang, Qi; Cui, Wei; Zou, Yifeng; Yuan, Xuanyi; Chen, Kexin
Abstract: Eu-doped Ca-α-SiAlON phosphors, featuring high phase purity, uniform particle size of 3–5 μm and good luminescent properties with a yellow emission spectrum under blue light excitation, were prepared by a highly efficient combustion synthesis (CS) method. A certain amount of NaCl was applied as an innovative additive to regulate and control the properties of synthesized phosphors. Further, the effects of NaCl additive in the CS system were systematically investigated and rational proposed. It was found that the effect on accelerating nitridation and crystallization played a dominant role in the reaction as the content of NaCl was less than 6 wt%, while the effect of absorbing reaction heat through vaporization was dominant with the further-increased content of NaCl. The intensity of the emission spectrum for the sample doped with 6 wt% of NaCl was remarkably enhanced, nearly 40% more than the sample which was not NaCl-doped. Moreover, a continuous blue-shift phenomenon in emission spectra was observed with the increased content of NaCl.